Apam Dot Company - Iskandar, Hasnidar; Asis, Nor Sahrinah; Sabi, Salasiah; Anas, Arlie Yana; Abd Kahar, Mohd Khairul Azhar (2012)
Apam cakes is a traditional cakes that had been know widely around the country. Apam usually used to served as a breakfast cakes and snacks during tea time. Instead of being an additional cakes, Apam is also had been the most important item in preparing a 'hantaran' in wedding ceremony. Apam Dot is die word that is derived from the word ''Apam polkadot'. It is inspired from fashion trend of using dots in their clothes. This trend we were used is to expect to catch the interest of the customer who are exposed to the new fashion trend especially for those who had a monthly salary. We were also providing delivery service for occasion such as party, weddings and many more. There will also service of making our Apam Dot as souvenir or gift as the customer wish. We believe that our business has the potential to success. This business plans will commence around early this year and will be the first stall in Sulaman Sentral Menggatal which specializing on Apam cakes. By existing this product at Sulaman Sentral, it will get many benefit people in Taman Kuala Menggatal, Taman Indah Permai, Taman Bukit Sepanggar and Taman Sri Indah.